2010
DOI: 10.1016/j.cell.2010.03.039
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Light-Regulated Retinal MicroRNAs Reveals Rapid Turnover as a Common Property of Neuronal MicroRNAs

Abstract: Adaptation to different levels of illumination is central to the function of the retina. Here, we demonstrate that levels of the miR-183/96/182 cluster, miR-204, and miR-211 are regulated by different light levels in the mouse retina. Concentrations of these microRNAs were downregulated during dark adaptation and upregulated in light-adapted retinas, with rapid decay and increased transcription being responsible for the respective changes. We identified the voltage-dependent glutamate transporter Slc1a1 as one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
439
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(474 citation statements)
references
References 74 publications
31
439
3
1
Order By: Relevance
“…[Mammalian neurons may be exceptional in having many miRNAs with short half-lives (31).] Cycling fly miRNAs now include mir-276a, which here we show oscillates throughout the day under LD conditions.…”
Section: Discussionmentioning
confidence: 69%
“…[Mammalian neurons may be exceptional in having many miRNAs with short half-lives (31).] Cycling fly miRNAs now include mir-276a, which here we show oscillates throughout the day under LD conditions.…”
Section: Discussionmentioning
confidence: 69%
“…Studies have shown that the rate of pri-miRs processing (maturation) is relatively constant while the rate of mature miRs catabolism varies with rapid turnover observed with certain neuronal miRs. 27 Our data show that miR-711 has a fast catabolism rate in RCN and cell injury has no significant impact on the decay rate. Thus, the increased miR-711 levels may reflect a rapid upregulation of miR-711 transcription, as supported by high pri-miRNA levels after etoposide treatment.…”
Section: Mir-711 Activates Neuronal Apoptosis B Sabirzhanov Et Almentioning
confidence: 61%
“…The panel also included a cluster of 88 possible candidate genes with expression patterns that were spatiotemporally related to retinal development 15,16 (Supplementary Table S2 online) and 32 abundant retinal miRNAs 17,18 (Supplementary Table S3 online). The targeted capture panel included a total of 252 genes, which comprised 3,376 exons and 615,029-nt coding regions.…”
Section: Design Of Targeted Capture Panelmentioning
confidence: 99%